Synthesis and investigation of quadruplex-DNA-binding, 9-O-substituted berberine derivatives - Becher, Jonas; Berdnikova, Daria V.; Ihmels, Heiko; Stremmel, Christopher (Beilstein Journal of Organic Chemistry, 2020)
A small series of five novel berberine derivatives was synthesized by the Cu-catalyzed click reaction of 9-propargyladenine with 9-O-(azidoalkyl)berberine derivatives. The association of the resulting berberine–adenine conjugates with representative quadruplex-forming oligonucleotides 22AG dA(G3TTA)3G3 and a2 d(ACAG4TGTG4)2 was examined with photometric and fluorimetric titrations, thermal DNA denaturation analysis, and CD spectroscopy. The results from the spectrometric titrations indicated the formation of 2:1 or 1:1 complexes (ligand:G4-DNA) with log Kb values of 10–11 (2:1) and 5–6 (1:1), which are typical for berberine derivatives. Notably, a clear relationship between the binding affinity of the ligands with the length of the alkyl linker chain, n, was not observed. However, depending on the structure, the ligands exhibited different effects when bound to the G4-DNA, such as fluorescent light-up effects and formation of ICD bands, which are mostly pronounced with a linker length of n = 4 (with a2) and n = 5 (with 22AG), thus indicating that each ligand–G4-DNA complex has a specific structure with respect to relative alignment and conformational flexibility of the ligand in the binding site. It was shown exemplarily with one representative ligand from the series that such berberine–adenine conjugates exhibit a selective binding, specifically a selectivity to quadruplex DNA in competition with duplex DNA, and a preferential thermal stabilization of the G4-DNA forms 22AG and KRAS. Notably, the experimental data do not provide evidence for a significant effect of the adenine unit on the binding affinity of the ligands, for example, by additional association with the loops, presumably because the adenine residue is sterically shielded by the neighboring triazole unit.
Keywords: berberine alkaloids; DNA ligands; DNA recognition; G4-DNA; nucleic acids

(untitled) - Neidle, S. (Nat. Rev. Chem., 2017)

(untitled) - Neidle, S. (J. Med. Chem., 2016)

(untitled) - Tateishi-Karimata, H.; Sugimoto, N. (Chem. Commun., 2020)

(untitled) - Cañeque, T.; Müller, S.; Rodriguez, R. (Nat. Rev. Chem., 2018)

(untitled) - Laguerre, A.; Wong, J. M. Y.; Monchaud, D. (Sci. Rep., 2016)

(untitled) - Chambers, V. S.; Marsico, G.; Boutell, J. M.; Di Antonio, M.; Smith, G. P.; Balasubramanian, S. (Nat. Biotechnol., 2015)

(untitled) - Verma, A.; Yadav, V. K.; Basundra, R.; Kumar, A.; Chowdhury, S. (Nucleic Acids Res., 2009)

(untitled) - Huppert, J. L.; Bugaut, A.; Kumari, S.; Balasubramanian, S. (Nucleic Acids Res., 2008)

(untitled) - Huppert, J. L.; Balasubramanian, S. (Nucleic Acids Res., 2007)

(untitled) - Collie, G. W.; Parkinson, G. N. (Chem. Soc. Rev., 2011)

(untitled) - Li, Y.; Syed, J.; Suzuki, Y.; Asamitsu, S.; Shioda, N.; Wada, T.; Sugiyama, H. (ChemBioChem, 2016)

(untitled) - Balasubramanian, S.; Hurley, L. H.; Neidle, S. (Nat. Rev. Drug Discovery, 2011)

(untitled) - Hänsel-Hertsch, R.; Di Antonio, M.; Balasubramanian, S. (Nat. Rev. Mol. Cell Biol., 2017)

(untitled) - Balasubramanian, S.; Neidle, S. (Curr. Opin. Chem. Biol., 2009)

(untitled) - Monsen, R. C.; Trent, J. O. (Biochimie, 2018)

(untitled) - Lee, H.-S.; Carmena, M.; Liskovykh, M.; Peat, E.; Kim, J.-H.; Oshimura, M.; Masumoto, H.; Teulade-Fichou, M.-P.; Pommier, Y.; Earnshaw, W. C.; Larionov, V.; Kouprina, N. (Cancer Res., 2018)

(untitled) - Nagatsugi, F.; Onizuka, K. (Chem. Lett., 2020)

(untitled) - Asamitsu, S.; Bando, T.; Sugiyama, H. (Chem. – Eur. J., 2019)

(untitled) - Dhamodharan, V.; Pradeepkumar, P. I. (ACS Chem. Biol., 2019)

(untitled) - O'Hagan, M. P.; Morales, J. C.; Galan, M. C. (Eur. J. Org. Chem., 2019)

(untitled) - Ruggiero, E.; Richter, S. N. (Nucleic Acids Res., 2018)

(untitled) - Duarte, A. R.; Cadoni, E.; Ressurreição, A. S.; Moreira, R.; Paulo, A. (ChemMedChem, 2018)

(untitled) - Gao, Y.; Wang, F.; Song, Y.; Liu, H. (Chin. Med. (London, U. K.), 2020)

(untitled) - Chu, M.; Chen, X.; Wang, J.; Guo, L.; Wang, Q.; Gao, Z.; Kang, J.; Zhang, M.; Feng, J.; Guo, Q.; Li, B.; Zhang, C.; et al. (Front. Pharmacol., 2018)

(untitled) - Kim, D.-G.; Choi, J.-W.; Jo, I.-J.; Kim, M.-J.; Lee, H.-S.; Hong, S.-H.; Song, H.-J.; Bae, G.-S.; Park, H.-S. (Mol. Med. Rep., 2020)

(untitled) - Li, Q.; He, W.; Zhang, L.; Zu, Y.; Zhu, Q.; Deng, X.; Zhao, T.; Gao, W.; Zhang, B. (Lett. Drug Des. Discovery, 2012)

(untitled) - Yi, Z.-B.; Yan, Y.; Liang, Y.-Z.; Bao, Z. (J. Pharm. Biomed. Anal., 2007)

(untitled) - Jin, F.; Xie, T.; Huang, X.; Zhao, X. (Pharm. Biol. (Abingdon, U. K.), 2018)

(untitled) - Wang, Y.; Zhang, S. (Biomed. Pharmacother., 2018)

(untitled) - Vieira, S.; Castelli, S.; Falconi, M.; Takarada, J.; Fiorillo, G.; Buzzetti, F.; Lombardi, P.; Desideri, A. (Int. J. Biol. Macromol., 2015)

(untitled) - Chu, S.-C.; Yu, C.-C.; Hsu, L.-S.; Chen, K.-S.; Su, M.-Y.; Chen, P.-N. (Mol. Pharmacol., 2014)

(untitled) - Lee, K.-H.; Lo, H.-L.; Tang, W.-C.; Hsiao, H. H.-y.; Yang, P.-M. (Sci. Rep., 2014)

(untitled) - Moraca, F.; Amato, J.; Ortuso, F.; Artese, A.; Pagano, B.; Novellino, E.; Alcaro, S.; Parrinello, M.; Limongelli, V. (Proc. Natl. Acad. Sci. U. S. A., 2017)

(untitled) - Papi, F.; Bazzicalupi, C.; Ferraroni, M.; Ciolli, G.; Lombardi, P.; Khan, A. Y.; Kumar, G. S.; Gratteri, P. (ACS Med. Chem. Lett., 2020)

(untitled) - Xiong, Y.-X.; Su, H.-F.; Lv, P.; Ma, Y.; Wang, S.-K.; Miao, H.; Liu, H.-Y.; Tan, J.-H.; Ou, T.-M.; Gu, L.-Q.; Huang, Z.-S. (Oncotarget, 2015)

(untitled) - Ma, Y.; Ou, T.-M.; Hou, J.-Q.; Lu, Y.-J.; Tan, J.-H.; Gu, L.-Q.; Huang, Z.-S. (Bioorg. Med. Chem., 2008)

(untitled) - Zhang, W.-J.; Ou, T.-M.; Lu, Y.-J.; Huang, Y.-Y.; Wu, W.-B.; Huang, Z.-S.; Zhou, J.-L.; Wong, K.-Y.; Gu, L.-Q. (Bioorg. Med. Chem., 2007)

(untitled) - Ferraroni, M.; Bazzicalupi, C.; Papi, F.; Fiorillo, G.; Guamán-Ortiz, L. M.; Nocentini, A.; Scovassi, A. I.; Lombardi, P.; Gratteri, P. (Chem. – Asian J., 2016)

(untitled) - Bhowmik, D.; Fiorillo, G.; Lombardi, P.; Suresh Kumar, G. (J. Mol. Recognit., 2015)

(untitled) - Bhowmik, D.; Hossain, M.; Buzzetti, F.; D’Auria, R.; Lombardi, P.; Kumar, G. S. (J. Phys. Chem. B, 2012)

(untitled) - Islam, M. M.; Basu, A.; Hossain, M.; Sureshkumar, G.; Hotha, S.; Suresh Kumar, G. (DNA Cell Biol., 2011)

(untitled) - Ma, Y.; Ou, T.-M.; Tan, J.-H.; Hou, J.-Q.; Huang, S.-L.; Gu, L.-Q.; Huang, Z.-S. (Bioorg. Med. Chem. Lett., 2009)

(untitled) - Wang, M.-Q.; Xu, J.; Zhang, L.; Liao, Y.; Wei, H.; Yin, Y.-Y.; Liu, Q.; Zhang, Y. (Bioorg. Med. Chem., 2019)

(untitled) - Funke, A.; Weisz, K. (Biochimie, 2019)

(untitled) - Lavrado, J.; Ohnmacht, S. A.; Correia, I.; Leitão, C.; Pisco, S.; Gunaratnam, M.; Moreira, R.; Neidle, S.; dos Santos, D. J. V. A.; Paulo, A. (ChemMedChem, 2015)

(untitled) - Singh, M.; Wang, S.; Joo, H.; Ye, Z.; Christison, K. M.; Hekman, R.; Vierra, C.; Xue, L. (Chem. Biol. Drug Des., 2020)

(untitled) - Tsvetkov, V. B.; Varizhuk, A. M.; Lizunova, S. A.; Nikolenko, T. A.; Ivanov, I. A.; Severov, V. V.; Belyaev, E. S.; Shitikov, E. A.; Pozmogova, G. E.; Aralov, A. V. (Org. Biomol. Chem., 2020)

(untitled) - Wang, S.; Yang, D.; Singh, M.; Joo, H.; Rangel, V. M.; Tran, A.; Phan, E.; Xue, L. (Eur. J. Med. Chem., 2019)

(untitled) - Zhang, L.; Er, J. C.; Li, X.; Heng, J. J.; Samanta, A.; Chang, Y.-T.; Lee, C.-L. K. (Chem. Commun., 2015)

(untitled) - Yu, Z.; Schonhoft, J. D.; Dhakal, S.; Bajracharya, R.; Hegde, R.; Basu, S.; Mao, H. (J. Am. Chem. Soc., 2009)

(untitled) - Dzubiel, D.; Ihmels, H.; Mahmoud, M. M. A.; Thomas, L. (Beilstein J. Org. Chem., 2014)

(untitled) - Saha, P.; Panda, D.; Dash, J. (Chem. Commun., 2019)

(untitled) - Wu, Y.-C.; Kuo, S.-W. (J. Mater. Chem., 2012)

(untitled) - Halimani, M.; Chandran, S. P.; Kashyap, S.; Jadhav, V. M.; Prasad, B. L. V.; Hotha, S.; Maiti, S. (Langmuir, 2009)

(untitled) - Megyesi, M.; Biczók, L.; Jablonkai, I. (J. Phys. Chem. C, 2008)

(untitled) - Díaz, M. S.; Freile, M. L.; Gutiérrez, M. I. (Photochem. Photobiol. Sci., 2009)

(untitled) - Huang, X.; Zhang, X.; Qian, T.; Ma, J.; Cui, L.; Li, C. (Beilstein J. Org. Chem., 2018)

(untitled) - Colina, A. N.; Díaz, M. S.; Gutiérrez, M. I. (J. Lumin., 2013)

(untitled) - Vorlíčková, M.; Kejnovská, I.; Sagi, J.; Renčiuk, D.; Bednářová, K.; Motlová, J.; Kypr, J. (Methods, 2012)

(untitled) - Rezler, E. M.; Seenisamy, J.; Bashyam, S.; Kim, M.-Y.; White, E.; Wilson, W. D.; Hurley, L. H. (J. Am. Chem. Soc., 2005)

(untitled) - Timmer, C. M.; Michmerhuizen, N. L.; Witte, A. B.; Van Winkle, M.; Zhou, D.; Sinniah, K. (J. Phys. Chem. B, 2014)

(untitled) - Schonhoft, J. D.; Das, A.; Achamyeleh, F.; Samdani, S.; Sewell, A.; Mao, H.; Basu, S. (Biopolymers, 2010)

(untitled) - Šmidlehner, T.; Piantanida, I.; Pescitelli, G. (Beilstein J. Org. Chem., 2018)

Linear Dichroism and Circular Dichroism - Norden, B.; Rodger, A.; Dafforn, T. (RSC Publishing, 2010)

(untitled) - Nordén, B.; Kurucsev, T. (J. Mol. Recognit., 1994)

(untitled) - Zhou, C.-Q.; Yang, J.-W.; Dong, C.; Wang, Y.-M.; Sun, B.; Chen, J.-X.; Xu, Y.-S.; Chen, W.-H. (Org. Biomol. Chem., 2016)

(untitled) - Li, Z.-Q.; Liao, T.-C.; Dong, C.; Yang, J.-W.; Chen, X.-J.; Liu, L.; Luo, Y.; Liang, Y.-Y.; Chen, W.-H.; Zhou, C.-Q. (Org. Biomol. Chem., 2017)

(untitled) - Tera, M.; Hirokawa, T.; Okabe, S.; Sugahara, K.; Seimiya, H.; Shimamoto, K. (Chem. – Eur. J., 2015)

(untitled) - Bortolozzi, R.; Ihmels, H.; Thomas, L.; Tian, M.; Viola, G. (Chem. – Eur. J., 2013)